Community-Acquired Pneumonia and Pneumonia Severity Index 20 (PSI-20): a study of 262 patients - Osuna, Alina (2006)
Background: Several prognostic models in patients with Community-aquired Pneumonia (CAP), such as the Pneumonia Severity Index 20 (PSI-20), have been devised, to assist the physician decide where to treat the patient initially. Objectives: The main goal of this work was to assess the adequacy of the risk classes defi ned according to the PSI-20 and hospital admission recommendations, as applied to our population. We also wanted to know the demographic characteristics and other factors which affect mortality.Methods: Retrospective study of all the patients admitted with CAP to our infi rmary over a one-year period. The 20 PSI variables were collected and the patients stratifi ed into risk classes (I-V).Results Overall, 262 inpatients with CAP were included; 60% were males, and 40% females, with a mean age of 72.9 years. No signifi cant differences were observed in mortality regarding sex, place of residence or presence of co-morbid conditions, but there was a signifi cant difference in relation to age.Treatment was empirical, with advantage for patients treated with a combination of antibiotics. The distribution of the patients across the risk classes was: Class I – 2.3%, Class II – 8.8%, Class III – 16.0%, Class IV – 45.0% and Class V – 27.9%. The mortality in each class in our series was similar to the mortality in the PSI study except for Class II (death of a patient with a severe co-morbid condition). Conclusions: The PSI-based model performed well when applied to our population. Most of the low risk-classes (I-III) patients could have been safely treated as outpatients.